2022
DOI: 10.1186/s12876-022-02329-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of neutrophil to lymphocyte ratio with preterm necrotizing enterocolitis: a retrospective case-control study

Abstract: Background There have been few studies on the relationship between the neutrophil to lymphocyte ratio (NLR) and necrotizing enterocolitis (NEC). We conducted a retrospective case-control study to investigate this relationship in preterm neonates. Methods A total of 199 preterm neonates diagnosed with NEC between January 2018 and January 2020 were included in this study. For each preterm infant with NEC that was admitted to the neonatal intensive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Lymphocyte is a kind of leukocyte, produced by the human lymphatic organ, with immune recognition and response function, its elevation represents the body infection or inflammatory response. Previous studies have found that platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) can be used to predict the severity of NEC (18,19), but lymphocytes have not been analyzed separately. In this study, lymphocytes in the surgical group were significantly lower than that in the conservative group, suggesting that lymphocytes were a protective factor in NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte is a kind of leukocyte, produced by the human lymphatic organ, with immune recognition and response function, its elevation represents the body infection or inflammatory response. Previous studies have found that platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) can be used to predict the severity of NEC (18,19), but lymphocytes have not been analyzed separately. In this study, lymphocytes in the surgical group were significantly lower than that in the conservative group, suggesting that lymphocytes were a protective factor in NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, The circulating neutrophil pool is depleted by migration to the intestine and peritoneum, and increased microvascular margins may be responsible for neutropenia ( 38 ). Neutropenia has been reported to be associated with severe NEC and poor clinical outcome ( 39 ). Lymphocytes, which play a key role in adaptive immunity, are derived from bone marrow haematopoietic stem cells and can be broadly classified as T-cells, B-cells and NK-cells.…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers, derived from routine complete blood counts, offer a non-invasive, cost-effective, and rapidly accessible means to evaluate systemic inflammation and infection risk. Preliminary studies in adult and pediatric populations have shown their potential to predict the severity and outcome of various inflammatory conditions [ 25 ]. However, their utility in the premature neonatal population is still a question of debate.…”
Section: Introductionmentioning
confidence: 99%